2013
DOI: 10.1177/0748233713475503
|View full text |Cite
|
Sign up to set email alerts
|

Carbon tetrachloride-induced lipid peroxidation and hyperglycemia in rat

Abstract: Launaea procumbens methanol extract (LPME) was evaluated against carbon tetrachloride (CCl4)-induced pancreatic oxidative damage and hyperglycemia in rats. Various doses of the extract were administered to rats after 48 h of CCl4 treatment (3 ml/kg bodyweight (bw); intraperitoneally, 20% CCl4/olive oil) twice a week for 4 weeks. Coadministration of various concentrations of LPME (100, 150 and 200 mg/kg) ameliorated the toxicity of CCl4 and reversed the serum level of enzymes (amylase and lipase), glucose and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 27 publications
1
14
0
1
Order By: Relevance
“… 39 In the same vein, intraperitoneal treatment with CCl 4 elicited hyperglycemia which was significantly (p < 0.05, p < 0.001 and p < 0.0001) reduced dose-dependently by oral treatments with 125–500 mg/kg/day of MIASE. Although, earlier studies have reported CCl 4 -induced hyperglycemia in rats treated with CCl 4 , 37,40,41 the marked reduction in FBG values, suggests the antihyperglycemic potential of MIASE in CCl 4 -induced hyperglycemia in rats. Although several studies have independently reported the antihyperglycemic effect of MIASE in different diabetic rat models , 3,4,42 this study reports for the first time the hypoglycemic effect of MIASE in the CCl 4 -induced hepatotoxic rats.…”
Section: Discussionmentioning
confidence: 77%
“… 39 In the same vein, intraperitoneal treatment with CCl 4 elicited hyperglycemia which was significantly (p < 0.05, p < 0.001 and p < 0.0001) reduced dose-dependently by oral treatments with 125–500 mg/kg/day of MIASE. Although, earlier studies have reported CCl 4 -induced hyperglycemia in rats treated with CCl 4 , 37,40,41 the marked reduction in FBG values, suggests the antihyperglycemic potential of MIASE in CCl 4 -induced hyperglycemia in rats. Although several studies have independently reported the antihyperglycemic effect of MIASE in different diabetic rat models , 3,4,42 this study reports for the first time the hypoglycemic effect of MIASE in the CCl 4 -induced hepatotoxic rats.…”
Section: Discussionmentioning
confidence: 77%
“…The chemicals commonly used to cause hepatic lesions and induce liver fibrosis include ethanol, carbon tetrachloride (CCl 4 )[52], thioacetamide[53], dimethylnitrosamine[54], and diethylnitrosamine[55]. A number of specific diets, such as the methionine- and choline-deficient diet[56], high-fat diet[57], and choline-deficient L -amino acid-defined diet[58], can be used to induce progression of NAFLD to hepatic fibrosis in experimental animals.…”
Section: Etiology and Pathological Characteristics Of Hepatic Fibrosismentioning
confidence: 99%
“…RSME prevented renal injuries with a subsequent restoration of all these parameters discussed above. This study is in relation to the studies of Khan, Khan [26] and Venkatanarayana, Sudhakara [27] who investigated how the administration of CCl 4 caused marked oxidative stress in kidneys. Serum creatinine, total bilirubin, gamma-GT and urea concentrations were significantly higher in the CCl 4 -treated rats.…”
Section: Discussionmentioning
confidence: 88%